FAKTOR-FAKTOR YANG MEMPENGARUHI CURAHAN WAKTU KERJA BURUH TANI WANITA PADA USAHATANI PADI SAWAH DI DESA MANIK RAMBUNG KECAMATAN SIDAMANIK KABUPATEN SIMALUNGUN - Siregar, Yemima; Khaswarina, Shorea; ', Rosnita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purposes of this research are to analyze the influance of age, number of children, wage level, width of, arable land area, work on area, education and experience level towards outporing work hour of women peasant and which factor that has the most dominant effect towards the work hour of women peasant at their lowland rice. The research used a survey method with purposive sampling. The samples of this research are 27 samples. Data analysis using Simple Linier Regression. The result showed that, the average outporing work hour of women peasant at their farm is 19,856 Hkp/growing season, age level variable, education and experience level do not have significant effect towards outporing work hour, meanwhile number of children, width of work on area, and wage level variable have significant effect towards outporing work hour of women peasant at their farm, and the most dominant independent variable in affecting the dependent variable is width of work on area. Â Keywords: Farm, Peasant Women, Outporing Work Time